Working for Oil Comparative Social Histories of Labor in the Global Oil Industry (Springer International Publishing, 2018)
This volume looks at the social history of oil workers to investigate how labor relations and experiences have shaped the emergence of this global extractive industry. Three inter-related themes are investigated by scholars: the political life of labor, the productive life of labor, and the urban and social life of labor. Compiled here is the work of scholars from a range of disciplines who situate labor and the social, political, and cultural dimensions of oil at the center of their analysis. In this comparative study, the historical and contemporary experiences of oil workers are analyzed from a number of key oil producing regions, including Latin America, the Middle East, Central Asia, the Caucasus, Europe and Africa.